(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
Launched in January 2024, the joint laboratory Verti-Lab is a strategic collaboration between the french company HydroQuest and the Technological Research and Development Unit of Ifremer. Its primary goal is to deepen the understanding of vertical axis technologies in order to make their industrial deployment easier for renewable energy production. The partnership focuses on bridging the gap between experimental and numerical modelling, with the aim of achieving a sustainable and responsible way to take advantage of tidal energy resources. One of the main areas of research is the experimental investigation of vertical axis turbines behaviour in the wave and current flume tank of Ifremer. The tests primarily aim to characterise the loads on vertical axis tidal turbines (VATTs) for physical analysis and numerical tools validation. Tests are conducted under a wide range of conditions, including varying incident flow velocities, aligned or misaligned currents, sheared velocity profiles, turbulence levels, and the presence of waves following or opposing the current. Following a brief introduction to the joint laboratory, including its organization and the initial results, we will present the influence of surface waves on the mechanical behaviour of a 1:20th-scale quadrirotor turbine. This paper will first detail the experimental setup and instrumentation used. Then, the mechanical behaviour of the turbine will be analyzed by examining its performance and loads under various surface wave conditions. These analyses will aim to demonstrate the impact of waves on loading and output fluctuations, emphasizing the interest of considering a torque model that accounts for wave contribution. To do so, we will propose representing the inertial effects on torque distribution using a model inspired by the Morison equation for hydrodynamic loading. The proposed formulation will be validated against experimental results for various configurations (waves, operating points, flow incidence/velocity). The databases are currently being processed to provide a detailed physical analysis.